Implementation of image compression on hardware platform - Koh, Aloysius Jia Lun (2018)
The image compression in which I use is JPEG. JPEG has been around for many decades and it has also been a standardized means of image transmission. For JPEG, there are lossless and lossy compression. Lossy compression will be implemented for this project. Lossy compression will result in a lower quality image as compared to the original, but it requires fewer resources and lower latency.